{Zircon U-Pb Chronostratigraphy and Provenance of the Cycladic Blueschist Unit and the Nature of the Contact With the Cycladic Basement on Sikinos and Ios Islands, Greece} - Poulaki, E.M.; Stockli, D. F.; Flansburg, M.E.; Soukis, K. (Tectonics, 2019)
©2019. American Geophysical Union. All Rights Reserved. Sikinos and Ios Islands, located in the Southern Cyclades, represent part of a Cenozoic metamorphic core complex system that exposes subduction-related metamorphic rocks in the highly extended back-arc region of the Hellenic subduction zone. These exhumed HP-LT metamorphic units are composed of Mesozoic metasedimentary rocks of the Cycladic Blueschist Unit (CBU) and the Paleozoic Cycladic Basement (CB). The magmatic and stratigraphic evolution of these units, as well as the nature of the contact between the CBU and CB, have remained poorly understood. We used zircon U-Pb dating to determine crystallization ages of the CB on Sikinos and the maximum deposition ages and detrital provenance of the metasedimentary units to reconstruct the Mesozoic to early Cenozoic stratigraphic and tectonic evolution of the CBU on both islands. The results reveal that the CB in Sikinos is composed of Cambrian-Silurian metasedimentary rocks intruded by Carboniferous granites and is overlain by metasedimentary rocks of the CBU with depositional ages spanning from Permo-Triassic to Late Cretaceous. The provenance data from the CBU records a long-lived tectonic evolution from Paleo-Tethys subduction and rifting, to passive margin formation, and to subduction of the Neo-Tethyan Pindos basin. The continuous stratigraphic record and provenance evolution from the CB into the CBU imply a para-autochthonous relationship. On NE Sikinos and Ios, stratigraphic constraints suggest older-over-younger relationships along cryptic-thrusts, supporting premetamorphic or synmetamorphic structural repetition of the CBU by imbrication, likely during subduction underplating.
Keywords: Cycladic Basement; Cycladic Blueschist Unit; detrital zircon; Hellenic subduction zone; Sikinos and Ios; zircon U-Pb geochronology